2020
DOI: 10.1088/1757-899x/715/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of twist angle on starting capability of a Savonius rotor – CFD analysis

Abstract: Starting capability is an important feature of any high performance wind turbine. This parameter is usually referred to the rotor static performance. In this paper, the results of CFD analysis on four Savonius rotor designs are presented with the objective of investigating the effect of twist angle on the starting capability. Essentially it is a comparison between a conventional Savonius rotor and three helical rotors with 0°, 90° and 180° twist angle. The proposed methodology was first validated against the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The maximum power coefficient value reaches to 0.142 at tip speed ratio of 0.78. Zakaria and Ibrahim (2020) studied on comparison between a conventional Savonius rotor and 0°, 90°, and 180° twist helical rotors. They found that the rotor with 0°, 90°, and 180° twist angle gives the maximum static torque coefficient of 0.434, 0.442, and 0.385.…”
Section: Review On Cfd Analysismentioning
confidence: 99%
“…The maximum power coefficient value reaches to 0.142 at tip speed ratio of 0.78. Zakaria and Ibrahim (2020) studied on comparison between a conventional Savonius rotor and 0°, 90°, and 180° twist helical rotors. They found that the rotor with 0°, 90°, and 180° twist angle gives the maximum static torque coefficient of 0.434, 0.442, and 0.385.…”
Section: Review On Cfd Analysismentioning
confidence: 99%
“…The rotor blades in this study were designed using an organic shape, and the shape was mathematically analyzed. Another study by A. Zakaria et al, 8 looked into how the 180 • twist helical Savonius rotor performed depending on the time step and time increment. Numerous numerical investigations of the effectiveness of VAWTs have contributed to the domain's expertise [9][10][11][12][13][14][15] .…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Semi-circular (Semi-circular) Figure 1. Semi-circular shape [18] This is the most common and frequently used form. The construction is straightforward, only using a cylinder split in half and arranged according to the shape of the letter 'S [19].…”
Section: Savonius Turbinementioning
confidence: 99%